Capillary electrophoresis separation of peptide diastereomers that contain methionine sulfoxide by dual cyclodextrin‐crown ether systems†. Issue 23 (20th October 2014) - Zhu, Qingfu; Heinemann, Stefan H.; Schönherr, Roland; Scriba, Gerhard K. E.
<x xml:space="preserve">Abstract</x> A dual‐selector system employing achiral crown ethers in combination with cyclodextrins has been developed for the separation of peptide diastereomers that contain methionine sulfoxide. The combinations of the crown ethers 15‐crown‐5, 18‐crown‐6, Kryptofix® 21 and Kryptofix® 22 and β‐cyclodextrin, carboxymethyl‐β‐cyclodextrin, and sulfated β‐cyclodextrin were screened at pH 2.5 and pH 8.0 using a 40/50.2 cm, 50 μm id fused‐silica capillary and a separation voltage of 25 kV. No diastereomer separation was observed in the sole presence of crown ethers, while only sulfated β‐cyclodextrin was able to resolve some peptide diastereomers at pH 8.0. Depending on the amino acid sequence of the peptide and the applied cyclodextrin, the addition of crown ethers, especially the Krpytofix® diaza‐crown ethers, resulted in significantly enhanced chiral recognition. Keeping one selector of the dual system constant, increasing concentrations of the second selector resulted in increased peak resolution and analyte migration time for peptide‐crown ether‐cyclodextrin combinations. The simultaneous diastereomer separation of three structurally related peptides was achieved using the dual selector system.